RETROSPECTIVE AUDIT OF THE FREELITE™ SERUM FREE LIGHT CHAIN (SFLC) ASSAY: TESTING PATTERNS, CONCORDANCE WITH SERUM AND URINE ELECTROPHORESIS/IMMUNOFIXATION AND CORRELATION WITH THE N LATEX FLC ASSAY. (February 2015) - Sasson, S. C.; McGill, K.; Wienholt, L.; Carr, A.; Brown, D.; Kelleher, A. D.; Breit, S. N.; Sewell, W. A.
Abstract : Aims: A retrospective audit of the Freelite™ SFLC assay was conducted to compare concordance with electrophoresis (EPG)/immunofixation (IFX) and correlation with the N latex FLC assay. Methods: 244 samples collected over 3.5 months were studied by nephelometry using the Freelite™ and N Latex FLC assays. Results were compared with serum (S) and/or urine (UEPG)/IFX. The precision and linearity of the N latex FLC assay were examined. Results: 94% of samples with kappa restriction, and 100% with lambda restriction had detectable paraprotein by SEPG/IFX or UEPG/IFX. The correlation between the two assays was good for kappa (R 2 = 0.935) but not lambda (R 2 = 0.775) especially when lambda was above the ULN (R 2 = 0.406). Agreement in the categorical diagnosis of restricted SFLC was good (Cohen's kappa = 0.701). In discordant samples the Freelite™ assay displayed higher agreement with IFX (53% vs 47%). The N latex FLC assay displayed good precision and linearity. Discussion: SFLC testing is popular despite traditional methods detecting paraproteins in most cases. Correlation between the Freelite™ and N latex FLC assays is better for kappa than lambda FLC. The two assays are not equivalent and the Freelite™ assay displays better agreement with IFX. Care should be taken by interpreting physicians and laboratories considering switching assays.